Supply chain management: maverick buying - Prokop, Darren (Henry Stewart Talks, 2024)
Vendor contracts, Ordering supplies, How GPOs work, Buyers intentions, Moral hazard, Monitoring employees, Incentives and penalties, Adverse selection, Insurance industry, Wages, Eliminating maverick buying